2011
DOI: 10.1353/hpu.2011.0047
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Health Care Access among Refugee Asylum Seekers

Abstract: Significant inter-related barriers exist at the individual, provider, and system levels. Strategies to improve access include targeting social programs and mental health services, expanding Medicaid eligibility/enrollment, promoting community-based organizations, enforcing the use of trained medical interpreters, and improving cultural competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
198
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(220 citation statements)
references
References 38 publications
9
198
1
3
Order By: Relevance
“…8,49,55,56 Aside from consultation fees, there appear to be other costs that serve as barriers, including the cost of transportation to appointments, difficulties paying for pharmaceuticals and other health-related expenses, 8 …”
Section: Affordabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…8,49,55,56 Aside from consultation fees, there appear to be other costs that serve as barriers, including the cost of transportation to appointments, difficulties paying for pharmaceuticals and other health-related expenses, 8 …”
Section: Affordabilitymentioning
confidence: 99%
“…The participants in the majority of the studies found navigating the healthcare system to be problematic due to inadequate knowledge of the availability of, and their eligibility for, health services. 49,50,[52][53][54][55][56] Problems cited were a lack of provision of health service information on arrival in the country, poor understanding of the concept of primary healthcare and referral pathways, and logistical difficulties in accessing a service. Social and community supports were seen as integral for providing information and resources to facilitate service access.…”
Section: Poor Health Literacy and Understanding Of The Health Systemmentioning
confidence: 99%
See 3 more Smart Citations